Proteomics and acetyl-proteomics reveal the antibacterial mechanism of berberine sulfate against methicillin-resistant Staphylococcus aureus - Hu, Zunli; Liu, Huiling; Chen, Mengying; Zhou, Jiafu; Bian, Yunxu; Lin, Chuyao; Liu, Shuming; Sun, Yewen; Tan, Minjia; Xu, Jun-Yu (Frontiers in Microbiology, 2026)
IntroductionThe rising prevalence of methicillin-resistant Staphylococcus aureus (MRSA) underscores an urgent need for novel antibacterial strategies. Although the natural antibacterial agent berberine sulfate exhibits inhibitory effects against MRSA, its precise molecular targets and mechanisms of action remain unclear.MethodsTo elucidate its mechanism, this study employed quantitative proteomics to analyze protein expression changes in MRSA before and after drug treatment. Acetylomics was further applied to investigate the impact on post-translational modifications. Key findings were functionally validated using site-directed mutagenesis and electrophoretic mobility shift assays (EMSA).ResultsQuantitative proteomics identified 255 differentially expressed proteins. Acetylomic analysis further revealed 38 differentially acetylated sites, among which berberine sulfate specifically induced acetylation at the K82 site of the global regulator SarA. Functional experiments demonstrated that the K82-mutated SarA protein showed significantly reduced binding affinity to the promoter of the virulence gene cluster agr.DiscussionThese results indicate that berberine sulfate mediates a comprehensive stress response in MRSA through extensive alterations in protein expression and post-translational modifications. Specifically, the acetylation of SarA at K82 and the consequent impairment of its DNA-binding capacity represent a potential core mechanism by which berberine sulfate suppresses MRSA virulence and adaptability.